(untitled) (Revista Direito em Debate, 2019)
The article deals with the natural basis of the legal system, that is, it considers natural law as part of the state legal system. This study initially seeks to clarify the main concepts related to the subject, and, from there, to expose the considerations of different philosophical-juridical currents that, respectively, were the basic source of writings and teachings related to natural law. In the end, there is also a confrontation with doctrinal positions that diverge from the position of considering natural law as part of social law and effectively applied. The study is developed through the analysis of several doctrinal works, and from it results two points to some extent opposite and paradoxical: on the one hand, an initial tendency of the growth of the less divine and more and more secular thought for the legal analysis; and, on the other hand, the factual response to the resumption of the divine foundation for the construction of a juridical order (as a reaction, for example, to the wars of the twentieth century).